A magnetic suspension heterogeneous catalyst and its preparation method and application
Through the coordinated use of biomass carbon and metal source and the composite treatment with hollow glass microspheres and sodium alginate, magnetic suspension heterogeneous catalysts were prepared, which solved the problems of inconvenient operation, narrow tolerance range and difficulty in recycling of existing catalysts. , achieving efficient catalysis and convenient recycling.
Patent Information
- Application Number
- CN202211550881.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-05
AI Technical Summary
During the use of existing heterogeneous catalysts, there are problems such as inconvenient operation, metal ion dissolution and narrow pH tolerance range, and the recovery process is difficult.
Using the coordinated use of biomass carbon and metal source, a magnetic suspension heterogeneous catalyst is prepared through co-precipitation and calcination, and mixed it with hollow glass microspheres and sodium alginate to form a spherical composite material to improve catalytic activity and Convenience of recycling.
The efficient catalytic activity of the catalyst is achieved, the wide pH tolerance range and the ease of recycling are solved, and the problems of inconvenient operation and narrow tolerance range of existing catalysts are solved.
Smart Images

Figure CN115990481B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysis and relates to a catalyst, in particular to a magnetic suspension heterogeneous catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, heterogeneous catalysts have attracted more and more attention due to their advantages such as low iron sludge production and recyclable catalysts compared to homogeneous catalysts. However, powdered heterogeneous catalysts have problems such as inconvenient operation, metal ion dissolution, and narrow pH tolerance range in actual use. In addition, the recovery process of non-magnetic heterogeneous powder catalysts is also difficult, and pure transition metal compound heterogeneous catalysts inevitably have agglomeration phenomena, which will lead to a reduction in the catalytic active sites of the catalyst and reduce the catalytic activity of the heterogeneous catalyst.
[0003] CN112473670A discloses a cobalt ferrite / montmorillonite / C catalyst that can efficiently activate persulfate, and its preparation method and application. The cobalt ferrite / montmorillonite catalyst is a composite of cobalt ferrite, montmorillonite and C, wherein the mass fraction of cobalt ferrite in the composite is 40-75%, and the mass fraction of montmorillonite in the composite is 20-50%. It has a large specific surface area, strong catalytic properties and good chemical stability, and can be used to activate persulfate to remove tetracycline. However, the composite catalyst prepared by the preparation method is in powder form, which is easy to lose and difficult to clean during actual use; and its pH tolerance range is only 3-8, which is not conducive to its further promotion and application.
[0004] CN114471654A discloses the preparation of a boron nitride material anchored cobalt ferrite composite catalyst and its application in catalytic degradation of oxytetracycline. Boron nitride material anchored cobalt ferrite composite catalysts BNMTs@CoFe2O4 and HBN@CoFe2O4 were prepared by coprecipitation and hydrothermal method. Both composite catalysts showed good degradation performance and cyclic stability to oxytetracycline, and had rich structures and oxygen-containing groups. However, the preparation method adopts hydrothermal method for preparation, which has high energy consumption and cumbersome preparation process; moreover, the catalyst obtained by the preparation method is in powder form, which has the defects of loss and difficulty in cleaning.
[0005] CN106268819A discloses an activated carbon-cobalt ferrite composite material, its preparation method and photocatalytic denitrification use. The preparation method weighs CoCl2·6H2O and FeCl3·9H2O in a molar ratio of 1:2 and dissolves them in 10mL of deionized water, then weighs the activated carbon and adds sodium hydroxide for coprecipitation, and then adds it to a reactor for hydrothermal reaction to obtain a composite material. However, the preparation method of the material is also a hydrothermal method with high energy consumption, and the prepared composite material is in powder form, which is inconvenient to use; and the cobalt ferrite and the activated carbon are connected by van der Waals force adsorption, which is easy to separate and fall off after long-term use, and the problem of metal ion dissolution cannot be solved.
[0006] Therefore, it is necessary to provide a magnetically suspended heterogeneous catalyst which has a simple preparation method, can be recycled, and has a wide pH tolerance range, and a preparation method and application thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a magnetic suspension heterogeneous catalyst and a preparation method and application thereof. The magnetic suspension heterogeneous catalyst obtained by the preparation method provided by the present invention has a wide pH tolerance range, is easy to recycle, has a long service life, and has excellent catalytic activity.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a magnetically suspended heterogeneous catalyst, the preparation method comprising the following steps:
[0010] (1) uniformly mixing the biochar, the metal source and the solvent, and co-precipitating to obtain a precipitate;
[0011] (2) The precipitate obtained in step (1) is washed, dried and calcined to obtain a biomass carbon composite material;
[0012] (3) uniformly mixing the hollow glass microspheres, the thickener solution and the biomass carbon composite material obtained in step (2) to obtain a mixed solution;
[0013] (4) The mixed solution obtained in step (3) is mixed with the solution and allowed to stand to obtain the magnetically suspended heterogeneous catalyst.
[0014] The preparation method provided by the present invention can evenly disperse the metal atoms in the metal source to the surface and pores of the biochar through the use of biochar and metal source, effectively slowing down the agglomeration of the metal catalyst; moreover, the coordinated use of the biochar and the metal source effectively improves the catalytic activity of the magnetic suspension heterogeneous catalyst. Moreover, the present invention mixes the biochar composite material with hollow glass microspheres and a thickener, and composites the powdered material into a spherical shape, overcoming the problem that the powder catalyst is inconvenient to use and difficult to fill the fixed bed, and can also effectively avoid the problem of metal dissolution of the metal catalyst species; the use of hollow glass microspheres brings a floating type to the magnetic suspension heterogeneous catalyst, which is conducive to the recovery of the magnetic suspension heterogeneous catalyst.
[0015] Preferably, the biomass charcoal in step (1) comprises any one of enteromorpha-based biochar, wood biochar, coconut shell biochar or straw biochar, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of enteromorpha-based biochar and wood biochar, a combination of wood biochar and coconut shell biochar, a combination of coconut shell biochar and straw biochar, a combination of enteromorpha-based biochar, wood biochar and coconut shell biochar, a combination of wood biochar, coconut shell biochar and straw biochar, or a combination of enteromorpha-based biochar, wood biochar, coconut shell biochar and straw biochar, preferably enteromorpha-based biochar.
[0016] The present invention uses biochar to prepare a magnetic suspension heterogeneous catalyst, which can not only make the metal in the metal source evenly distributed on the surface and in the pores of the biochar to avoid the agglomeration of metal ions, but also make the biochar and the metal produce a synergistic effect to improve the catalytic activity. The biochar of the present invention is preferably enteromorpha-based biochar, which has high N and P content and rich polar groups such as -OH, -COOH and -NH2. After being carbonized into biochar, it has the characteristics of better coordination, complexation and adsorption of transition metals than other single lignin biochars, and is also more conducive to exerting the synergistic catalytic effect of biochar and transition metals.
[0017] Preferably, the method for preparing biochar in step (1) comprises the following steps: carbonizing biomass at 360-420° C. for 1.5-2.5 hours.
[0018] The carbonization temperature is 360-420°C, for example, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C or 420°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] The carbonization time is 1.5-2.5 h, for example, 1.5 h, 1.6 h, 1.8 h, 2 h, 2.1 h, 2.4 h or 2.5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the method for preparing the biochar in step (1) further comprises acid modification after carbonization: the carbonized biomass is soaked in an acid solution, and then washed and dried in sequence to obtain the biochar.
[0021] The present invention can wash away inorganic salts remaining in the carbon matrix through acid modification to achieve the purpose of purifying the carbon matrix. On the other hand, it can effectively expand the pores of the carbon matrix, increase the specific surface area and facilitate the subsequent adsorption of transition metals.
[0022] Preferably, the acid solution comprises any one of hydrochloric acid solution, nitric acid solution or sulfuric acid solution, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of hydrochloric acid solution and nitric acid solution, a combination of nitric acid solution and sulfuric acid solution, a combination of hydrochloric acid solution and sulfuric acid solution, or a combination of hydrochloric acid solution, nitric acid solution and sulfuric acid solution.
[0023] Preferably, the acid solution contains H + The concentration is 0.8-1.2 mol / L, for example, it can be 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L or 1.2 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the soaking time is 1.8-2.4 h, for example, 1.8 h, 2 h, 2.1 h, 2.2 h or 2.4 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the drying temperature is 55-65° C. and the drying time is 10-15 h.
[0026] The drying temperature after acid modification of the present invention is 55-65°C, for example, it can be 55°C, 56°C, 58°C, 60°C, 61°C, 62°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] The drying time after acid modification of the present invention is 10-15 hours, for example, it can be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the method for preparing biochar in step (1) further comprises ultrasonic alcohol washing after acid modification.
[0029] Preferably, the metal source in step (1) comprises an iron source and / or a cobalt source, preferably a combination of an iron source and a cobalt source.
[0030] Preferably, the molar ratio of Fe to Co in the metal source in step (1) is (1.8-2.2):1.
[0031] The metal source of the present invention is Fe and Co in a molar ratio of (1.8-2.2): 1. After co-precipitation with biochar, CoFe2O4 can be uniformly dispersed on the surface and pores of biochar, effectively slowing down the agglomeration of CoFe2O4; moreover, biochar can exert a synergistic catalytic effect with CoFe2O4, so that the magnetic suspension heterogeneous catalyst has a higher catalytic efficiency. In addition, CoFe2O4 is uniformly loaded on Enteromorpha biochar, which can effectively improve the isoelectric point of Enteromorpha biochar, which is conducive to the adsorption of antibiotics such as lomefloxacin. While improving the catalytic effect, the pH tolerance range of the composite material is effectively expanded, and the application range of the composite catalytic material is expanded.
[0032] Preferably, the iron source comprises FeCl3 and / or Fe(NO3)3.
[0033] Preferably, the cobalt source comprises CoCl2 and / or Co(NO3)2.
[0034] Preferably, the mass ratio of the biochar to the solvent in step (1) is 1:(21-28), for example, it can be 1:21, 1:22, 1:24, 1:25, 1:27 or 1:28, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the mass ratio of the biochar in step (1) to Co in the metal source is (3-5):1, for example, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the pH value of the coprecipitation in step (1) is 9.5-11.5, for example, it can be 9.5, 9.7, 9.9, 10, 10.2, 10.4, 10.5, 11 or 11.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the coprecipitation temperature in step (1) is 60-70°C, for example, 60°C, 62°C, 65°C, 66°C, 68°C or 70°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the coprecipitation time in step (1) is 1.5-2.5 h, for example, 1.5 h, 1.6 h, 1.8 h, 2 h, 2.1 h, 2.4 h or 2.5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] The washing in step (2) of the present invention is conventional washing, which illustratively includes but is not limited to washing with deionized water and anhydrous ethanol alternately to remove impurities until the washing liquid is neutral.
[0040] Preferably, the drying temperature in step (2) is 75-85°C, for example, it can be 75°C, 77°C, 78°C, 80°C, 81°C, 82°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the drying time in step (2) is 10-15 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] Preferably, the calcination in step (2) comprises a starting temperature of 200-240°C and an end temperature of 660-700°C.
[0043] The starting temperature of the calcination in step (2) of the present invention is 200-240°C, for example, it can be 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C or 240°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0044] The terminal temperature of the calcination in step (2) of the present invention is 660-700°C, for example, it can be 660°C, 665°C, 670°C, 675°C, 680°C, 685°C, 690°C, 695°C or 700°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the calcination in step (2) includes at least 3 heat preservation processes.
[0046] Preferably, the calcination in step (2) includes 6 heat preservation processes.
[0047] Preferably, the insulation process lasts for 1.8-2.4 hours, for example, 1.8 hours, 2 hours, 2.1 hours, 2.2 hours or 2.4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, the mass ratio of the hollow glass microspheres to the biomass carbon composite material in step (3) is (0.8-1.2):1, for example, it can be 0.8:1, 0.9:1, 1:1, 1.1:1 or 1.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the solid-to-liquid ratio of the biomass charcoal composite material to the thickener solution in step (3) is 1:(20-30), and the unit of the solid-to-liquid ratio is g / mL, for example, it can be 1:20, 1:21, 1:22, 1:24, 1:25, 1:27, 1:28 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the concentration of the thickener solution in step (3) is 2-3wt%, for example, 2wt%, 2.1wt%, 2.4wt%, 2.5wt%, 2.7wt%, 2.8wt% or 3wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] Preferably, the thickener in the thickener solution in step (3) comprises any one of sodium alginate, chitosan or chitosan, or a combination of at least two of them, preferably sodium alginate.
[0052] Preferably, the mixing in step (4) is performed by adding the mixed solution dropwise into the solution.
[0053] Preferably, the dropping speed is 2-4 mL / min, for example, 2 mL / min, 2.5 mL / min, 3 mL / min, 3.5 mL / min or 4 mL / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0054] Preferably, the solution in step (4) comprises a calcium salt solution or a sodium hydroxide solution.
[0055] Preferably, the calcium salt in the calcium salt solution includes calcium chloride and / or calcium nitrate.
[0056] Preferably, the concentration of the calcium salt solution is 2-4wt%, for example, 2wt%, 2.5wt%, 3wt%, 3.5wt% or 4wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the standing time in step (4) is 50-70 min, for example, 50 min, 55 min, 60 min, 65 min or 70 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] As a preferred technical solution of the preparation method described in the first aspect, the preparation method comprises the following steps:
[0059] (1) uniformly mixing Enteromorpha-based biochar, a metal source and water, and co-precipitating at a temperature of 60-70° C. for 1.5-2.5 hours to obtain a precipitate; the termination pH value of the co-precipitation is 9.5-11.5; the mass ratio of Enteromorpha-based biochar to water is 1:(21-28); the mass ratio of Enteromorpha-based biochar to Co in the metal source is (3-5):1; the metal source is a combination of an iron source and a cobalt source, wherein the molar ratio of Fe to Co is (1.8-2.2):1;
[0060] The preparation method of the enteromorpha-based biochar comprises: carbonizing the enteromorpha at 360-420° C. for 1.5-2.5 h, and then heating the enteromorpha at H + Soaking in an acid solution with a concentration of 0.8-1.2 mol / L for 1.8-2.4 hours, washing, drying at 55-65° C. for 10-15 hours, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar;
[0061] (2) The precipitate obtained in step (1) is washed, dried at 75-85° C. for 10-15 h, and calcined to obtain a biomass carbon composite material; the starting temperature of the calcination is 200-240° C., the end temperature is 660-700° C., and the calcination process includes at least 3 insulation processes;
[0062] (3) uniformly mixing the hollow glass microspheres, the sodium alginate solution with a concentration of 2-3wt% and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the biomass carbon composite material is (0.8-1.2):1; the solid-liquid ratio of the biomass carbon composite material to the sodium alginate solution is 1:(20-30), and the unit of the solid-liquid ratio is g / mL;
[0063] (4) The mixed solution obtained in step (3) is added dropwise to a calcium salt solution having a concentration of 2-4 wt% at a rate of 2-4 mL / min, and allowed to stand for 50-70 min to obtain the magnetic suspension heterogeneous catalyst.
[0064] In a second aspect, the present invention provides a magnetically suspended heterogeneous catalyst, wherein the magnetically suspended heterogeneous catalyst is obtained by the preparation method described in the first aspect.
[0065] Preferably, the magnetic suspension heterogeneous catalyst provided by the present invention is a composite material of biochar, CoFe2O4, sodium alginate and hollow glass microspheres.
[0066] In the magnetic suspension heterogeneous catalyst provided by the present invention, CoFe2O4 is uniformly dispersed on the surface and pores of the biochar, effectively slowing down the particle agglomeration of CoFe2O4; moreover, the biochar and CoFe2O4 work together to improve the catalytic effect of the obtained magnetic suspension heterogeneous catalyst.
[0067] Furthermore, the magnetically suspended heterogeneous catalyst of the present invention utilizes hollow glass microspheres to transform the powder state into a floating spherical state, which is beneficial for catalyst recovery and can also effectively avoid the problem of easy dissolution of transition metals in the powdered catalyst.
[0068] In a third aspect, the present invention provides an application of the magnetically suspended heterogeneous catalyst described in the first aspect, wherein the magnetically suspended heterogeneous catalyst is used to degrade organic pollutants.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] (1) The preparation method provided by the present invention can evenly disperse the metal atoms in the metal source to the surface and pores of the biomass carbon through the use of biomass carbon and metal source, effectively slowing down the agglomeration of the metal catalyst; moreover, the coordinated use of the biomass carbon and the metal source effectively improves the catalytic activity of the magnetic suspension heterogeneous catalyst; the present invention mixes the biomass carbon composite material with hollow glass microspheres and sodium alginate, and composites the powdered material into a spherical shape, thereby overcoming the problem that the powdered catalyst is inconvenient to use and difficult to fill in a fixed bed, and can also effectively avoid the problem of metal dissolution of the metal catalyst; the use of hollow glass microspheres makes the magnetic suspension heterogeneous catalyst floatable, which is conducive to the recovery of the magnetic suspension heterogeneous catalyst;
[0071] (2) In the magnetically suspended heterogeneous catalyst provided by the present invention, CoFe2O4 is uniformly dispersed on the surface and pores of the biochar, which effectively slows down the agglomeration of CoFe2O4 particles; moreover, the biochar and CoFe2O4 work together to improve the catalytic effect of the obtained magnetically suspended heterogeneous catalyst; moreover, the magnetically suspended heterogeneous catalyst of the present invention utilizes hollow glass microspheres to transform the powder state into a floating spherical state, which is beneficial to the recovery of the catalyst and can also effectively avoid the problem of easy dissolution of transition metals in the powdered catalyst.
[0072] (3) In the magnetic suspension heterogeneous catalyst provided by the present invention, CoFe2O4 is uniformly dispersed on the surface and pores of the biochar, which effectively improves the isoelectric point of the biochar, is beneficial to the adsorption of antibiotics by the magnetic suspension heterogeneous catalyst, and effectively expands the pH tolerance range of the magnetic suspension heterogeneous catalyst while improving the catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 XRD diagrams of the magnetic suspension heterogeneous catalyst provided in Example 1, the CoFe2O4 provided in Comparative Example 1, and the biomass carbon material provided in Comparative Example 2;
[0074] Figure 2Infrared spectra of the magnetic suspension heterogeneous catalyst provided in Example 1, the CoFe2O4 provided in Comparative Example 1, and the biomass carbon material provided in Comparative Example 2;
[0075] Figure 3 This is a scanning electron microscope image of the magnetically suspended heterogeneous catalyst provided in Example 1;
[0076] Figure 4 A scanning electron microscope image of CoFe2O4 provided for Comparative Example 1;
[0077] Figure 5 A scanning electron microscope image of the biomass carbon material provided for Comparative Example 2;
[0078] Figure 6 This is the EDS element distribution diagram of the magnetic suspension heterogeneous catalyst provided in Example 1;
[0079] Figure 7 The elemental composition diagram of the magnetic suspension heterogeneous catalyst provided in Example 1;
[0080] Figure 8 , Fig. 9 This is a transmission electron microscopy image of the magnetically suspended heterogeneous catalyst provided in Example 1;
[0081] Fig.10 Degradation curves of the magnetic suspension heterogeneous catalyst provided in Example 1 at different pH values;
[0082] Fig.11 Zeta potential diagrams of the magnetically suspended heterogeneous catalyst provided in Example 1, the CoFe2O4 provided in Comparative Example 1, and the biomass carbon material provided in Comparative Example 2.
[0083] Fig.12 This is a graph for evaluating the cyclic performance of the magnetically suspended heterogeneous catalyst provided in Example 1. DETAILED DESCRIPTION
[0084] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0085] Example 1
[0086] This embodiment provides a method for preparing a magnetically suspended heterogeneous catalyst, the preparation method comprising the following steps:
[0087] (1) uniformly mixing Enteromorpha-based biochar, a metal source and water, and co-precipitating at a temperature of 65° C. for 2 hours to obtain a precipitate; the termination pH value of the co-precipitation is 10.5; the mass ratio of Enteromorpha-based biochar to water is 1:25; the mass ratio of the Enteromorpha-based biochar to Co in the metal source is 4:1; the metal source is a combination of ferric chloride and cobalt chloride, wherein the molar ratio of Fe to Co is 2:1;
[0088] The preparation method of the enteromorpha-based biochar comprises: carbonizing commercially available dry enteromorpha strips at 400°C for 2 hours, and then heating them in H + soaking in 1 mol / L hydrochloric acid for 2 hours, washing, drying at 60° C. for 12 hours, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar;
[0089] (2) The precipitate obtained in step (1) is washed, dried at 80°C for 12 h, and calcined to obtain a biomass carbon composite material; the starting temperature of the calcination is 200°C, the end temperature is 700°C, and the calcination process is carried out at 200°C, 300°C, 400°C, 500°C, 600°C and 700°C, respectively, and the insulation time for each time is 2.1 h;
[0090] (3) uniformly mixing the hollow glass microspheres, a sodium alginate solution having a concentration of 2.5 wt % and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the biomass carbon composite material is 1:1; the solid-liquid ratio of the biomass carbon composite material to the sodium alginate solution is 1:25, and the unit of the solid-liquid ratio is g / mL;
[0091] (4) The mixed solution obtained in step (3) was added dropwise to a 3 wt % calcium chloride solution at a rate of 3 mL / min and allowed to stand for 60 min to obtain the magnetically suspended heterogeneous catalyst.
[0092] Example 2
[0093] This embodiment provides a method for preparing a magnetically suspended heterogeneous catalyst, the preparation method comprising the following steps:
[0094] (1) uniformly mixing Enteromorpha-based biochar, a metal source and water, and co-precipitating at a temperature of 60° C. for 2.5 hours to obtain a precipitate; the termination pH value of the co-precipitation is 9.5; the mass ratio of Enteromorpha-based biochar to water is 1:21; the mass ratio of the Enteromorpha-based biochar to Co in the metal source is 3:1; the metal source is a combination of ferric chloride and cobalt chloride, wherein the molar ratio of Fe to Co is 1.8:1;
[0095] The preparation method of the Enteromorpha-based biochar is the same as that in Example 1;
[0096] (2) The precipitate obtained in step (1) was washed, dried at 75° C. for 15 h, and calcined to obtain a biomass carbon composite material; the starting temperature of the calcination was 220° C., the end temperature was 680° C., and the calcination process was carried out at 220° C., 320° C., 420° C., 480° C., 580° C., and 680° C., respectively, and each insulation time was 1.8 h;
[0097] (3) uniformly mixing the hollow glass microspheres, a sodium alginate solution having a concentration of 2 wt % and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the biomass carbon composite material is 1.2:1; the solid-liquid ratio of the biomass carbon composite material to the sodium alginate solution is 1:30, and the unit of the solid-liquid ratio is g / mL;
[0098] (4) The mixed solution obtained in step (3) was added dropwise to a 2 wt% calcium chloride solution at a rate of 2 mL / min and allowed to stand for 70 min to obtain the magnetically suspended heterogeneous catalyst.
[0099] Example 3
[0100] This embodiment provides a method for preparing a magnetically suspended heterogeneous catalyst, the preparation method comprising the following steps:
[0101] (1) uniformly mixing Enteromorpha-based biochar, a metal source and water, and co-precipitating at a temperature of 70° C. for 1.5 h to obtain a precipitate; the termination pH value of the co-precipitation is 11.5; the mass ratio of Enteromorpha-based biochar to water is 1:28; the mass ratio of the Enteromorpha-based biochar to Co in the metal source is 5:1; the metal source is a combination of ferric chloride and cobalt chloride, wherein the molar ratio of Fe to Co is 2.2:1;
[0102] The preparation method of the Enteromorpha-based biochar is the same as that in Example 1;
[0103] (2) The precipitate obtained in step (1) was washed, dried at 85°C for 10 h, and calcined to obtain a biomass carbon composite material; the starting temperature of the calcination was 240°C, the end temperature was 660°C, and the calcination process was carried out at 240°C, 280°C, 380°C, 520°C, 620°C, and 660°C, respectively, and the insulation time for each time was 2.4 h;
[0104] (3) uniformly mixing the hollow glass microspheres, a sodium alginate solution having a concentration of 3 wt % and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the biomass carbon composite material is 0.8:1; the solid-liquid ratio of the biomass carbon composite material to the sodium alginate solution is 1:20, and the unit of the solid-liquid ratio is g / mL;
[0105] (4) The mixed solution obtained in step (3) was added dropwise to a 4 wt % calcium chloride solution at a rate of 4 mL / min and allowed to stand for 50 min to obtain the magnetically suspended heterogeneous catalyst.
[0106] Example 4
[0107] This embodiment provides a method for preparing a magnetic suspension heterogeneous catalyst, wherein the preparation method of the Enteromorpha-based biochar is as follows: carbonizing commercially available dry Enteromorpha strips at 360°C for 2.5 hours, and then heating them in H + soaking in 0.8 mol / L hydrochloric acid for 2.4 h, washing, drying at 55° C. for 15 h, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar;
[0108] The rest are the same as in Example 1.
[0109] Example 5
[0110] This embodiment provides a method for preparing a magnetic suspension heterogeneous catalyst, wherein the preparation method of the Enteromorpha-based biochar is as follows: carbonizing commercially available dry Enteromorpha strips at 420°C for 1.5 h, and then heating them in H + Soaking in 1.2 mol / L hydrochloric acid for 1.8 hours, washing, drying at 65° C. for 10 hours, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar;
[0111] The rest are the same as in Example 1.
[0112] Example 6
[0113] This embodiment provides a method for preparing a magnetic suspension heterogeneous catalyst, wherein the preparation method of the Enteromorpha-based biochar is as follows: carbonizing commercially available dry Enteromorpha strips at 400° C. for 2 h, drying at 60° C. for 12 h, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar;
[0114] The rest are the same as in Example 1.
[0115] Example 7
[0116] This embodiment provides a method for preparing a magnetically suspended heterogeneous catalyst, which is the same as that of Embodiment 1 except that the enteromorpha is replaced by corn stalks.
[0117] Example 8
[0118] This embodiment provides a method for preparing a magnetically suspended heterogeneous catalyst, which is the same as that of Embodiment 1 except that Enteromorpha is replaced by coconut shell.
[0119] Example 9
[0120] This example provides a method for preparing a magnetically suspended heterogeneous catalyst, which is the same as Example 1 except that the molar amount of Co is replaced by Mn.
[0121] Example 10
[0122] This embodiment provides a method for preparing a magnetic suspension heterogeneous catalyst, except that sodium alginate is replaced by commercial chitosan ((C6H 11 NO4) n , viscosity 300mPa·s), the rest are the same as in Example 1.
[0123] Comparative Example 1
[0124] This comparative example provides a CoFe2O4, the preparation method of which comprises the following steps:
[0125] (1) uniformly mixing a metal source and water, and subjecting the mixture to precipitation for 2 h at a pH value of 10 and a temperature of 65° C. to obtain a precipitate; the amount of the metal source and water used was the same as in Example 1;
[0126] (2) The precipitate obtained in step (1) is washed, dried at 80°C for 12 h and calcined to obtain CoFe2O4.
[0127] The calcination procedure in this comparative example is the same as that in Example 1.
[0128] Comparative Example 2
[0129] This comparative example provides a biomass carbon material, and the preparation method of the biomass carbon material comprises the following steps:
[0130] (1) uniformly mixing Enteromorpha-based biochar and water, and precipitating them for 2 h at a pH value of 10 and a temperature of 65°C to obtain a precipitate; the mass ratio of Enteromorpha-based biochar to water was 1:25;
[0131] The preparation method of the Enteromorpha-based biochar is the same as that in Example 1;
[0132] (2) The precipitate obtained in step (1) is washed, dried at 80° C. for 12 h, and calcined to obtain a biomass carbon material.
[0133] The calcination procedure in this comparative example is the same as that in Example 1.
[0134] Comparative Example 3
[0135] This comparative example provides a CoFe2O4 composite material, and the preparation method thereof comprises the following steps:
[0136] (1) uniformly mixing a metal source and water, and subjecting the mixture to precipitation for 2 h at a pH value of 10 and a temperature of 65° C. to obtain a precipitate; the amount of the metal source and water used was the same as in Example 1;
[0137] (2) The precipitate obtained in step (1) was washed, dried at 80° C. for 12 h, and calcined to obtain CoFe2O4;
[0138] (3) uniformly mixing the hollow glass microspheres, a sodium alginate solution having a concentration of 2.5 wt % and the CoFe2O4 obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the CoFe2O4 is 1:1; the solid-liquid ratio of the CoFe2O4 to the sodium alginate solution is 1:25, and the unit of the solid-liquid ratio is g / mL;
[0139] (4) The mixed solution obtained in step (3) was added dropwise to a 3 wt% calcium chloride solution and allowed to stand for 60 min to obtain the CoFe2O4 composite material.
[0140] The calcination procedure in this comparative example is the same as that in Example 1.
[0141] Comparative Example 4
[0142] This comparative example provides a biomass carbon composite material, and the preparation method thereof comprises the following steps:
[0143] (1) uniformly mixing Enteromorpha-based biochar and water, and precipitating them for 2 h at a pH value of 10 and a temperature of 65°C to obtain a precipitate; the mass ratio of Enteromorpha-based biochar to water was 1:25;
[0144] The preparation method of the Enteromorpha-based biochar is the same as that in Example 1;
[0145] (2) The precipitate obtained in step (1) is washed, dried at 80° C. for 12 h, and calcined to obtain a biomass carbon material;
[0146] (3) uniformly mixing the hollow glass microspheres, a sodium alginate solution having a concentration of 2.5 wt % and the biomass carbon material obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the biomass carbon material is 1:1; the solid-liquid ratio of the biomass carbon material to the sodium alginate solution is 1:25, and the unit of the solid-liquid ratio is g / mL;
[0147] (4) The mixed solution obtained in step (3) is added dropwise to a 3 wt% calcium chloride solution and allowed to stand for 60 minutes to obtain the biomass carbon composite material.
[0148] The calcination procedure in this comparative example is the same as that in Example 1.
[0149] Comparative Example 5
[0150] This comparative example provides a method for preparing a heterogeneous catalyst, and the preparation method comprises the following steps:
[0151] (1) uniformly mixing Enteromorpha-based biochar, a metal source and water, co-precipitating for 2 hours at a pH value of 10 and a temperature of 65° C. to obtain a precipitate; the mass ratio of Enteromorpha-based biochar to water is 1:25; the ratio of the molar amount of Enteromorpha-based biochar to the total molar amount of metal atoms in the metal source is 1:1; the metal source is a combination of ferric chloride and cobalt chloride, wherein the molar ratio of Fe to Co is 2:1;
[0152] The preparation method of the Enteromorpha-based biochar comprises: carbonizing the Enteromorpha at 400°C for 2 hours, and then heating the Enteromorpha at H + soaking in 1 mol / L hydrochloric acid for 2 hours, washing, drying at 60° C. for 12 hours, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar;
[0153] (2) The precipitate obtained in step (1) is washed, dried at 80° C. for 12 h, and calcined to obtain a biomass carbon composite material;
[0154] (3) uniformly mixing a sodium alginate solution having a concentration of 2.5 wt% and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; the solid-liquid ratio of the biomass carbon composite material to the sodium alginate solution is 1:25, and the unit of the solid-liquid ratio is g / mL;
[0155] (4) The mixed solution obtained in step (3) was added dropwise to a 3 wt% calcium chloride solution and allowed to stand for 60 min to obtain the heterogeneous catalyst.
[0156] The calcination procedure in this comparative example is the same as that in Example 1.
[0157] Performance Characterization
[0158] (1) The XRD patterns of the magnetic suspension heterogeneous catalyst provided in Example 1, the CoFe2O4 provided in Comparative Example 1, and the biomass carbon material provided in Comparative Example 2 are shown in FIG. Figure 1 As shown;
[0159] Depend on Figure 1 It can be seen that the biomass carbon material provided in Comparative Example 2 has the crystal plane structure of graphite carbon; the diffraction peaks of CoFe2O4 provided in Comparative Example 1 correspond to the (220), (311), (400) and (511) crystal plane structures (PDF#22-1086); the XRD pattern of the magnetic suspension heterogeneous catalyst provided in Example 1 has typical characteristics of spinel ferrite CoFe2O4 and graphite carbon, indicating that the magnetic suspension heterogeneous catalyst obtained in Example 1 successfully realizes the composite of CoFe2O4 and biomass carbon.
[0160] (2) The infrared spectra of the magnetic suspension heterogeneous catalyst provided in Example 1, the CoFe2O4 provided in Comparative Example 1, and the biomass carbon material provided in Comparative Example 2 are shown in FIG. Figure 2 As shown;
[0161] Depend on Figure 2 It can be seen that the magnetic suspension heterogeneous catalyst provided in Example 1 has characteristic peaks of ferrite CoFe2O4 and biomass carbon material, indicating that the magnetic suspension heterogeneous catalyst obtained in Example 1 successfully realizes the composite of CoFe2O4 and biomass carbon.
[0162] (3) The saturation magnetization intensity of the magnetically suspended heterogeneous catalysts provided in Examples 1-10, the CoFe2O4 provided in Comparative Example 1, the biomass carbon material provided in Comparative Example 2, the CoFe2O4 composite material provided in Comparative Example 3, the biomass carbon composite material provided in Comparative Example 4, and the heterogeneous catalyst provided in Comparative Example 5 was tested using a Quantachrome DynaCool vibrating sample magnetometer. The results are shown in Table 1.
[0163] Table 1
[0164]
[0165]
[0166] It can be seen from Table 1 that the magnetic suspension heterogeneous catalyst provided by the present invention has a relatively high saturation magnetic induction intensity, is an excellent recyclable material, and has a good application prospect.
[0167] (4) The SEM image of the magnetic suspension heterogeneous catalyst provided in Example 1 is as follows Figure 3 As shown, EDS Figure 6 The element distribution diagram is shown in Figure 7 As shown in the transmission electron microscopy image Figure 8 , Fig. 9 As shown; Comparative Example 1 provides a SEM image of CoFe2O4 as shown Figure 4 As shown; the SEM image of the biomass carbon material provided in Comparative Example 2 is as shown Figure 5 As shown;
[0168] Depend on Figure 3-5 It can be seen that the pure biomass carbon material presents a smooth layered structure, and the pure CoFe2O4 particles have obvious aggregation phenomenon; while in the magnetic suspension heterogeneous catalyst, the CoFe2O4 particles are evenly dispersed on the surface of the biomass carbon, and there is no obvious aggregation phenomenon; thus, it can be seen that the composite of the biomass carbon and CoFe2O4 of the present invention can effectively avoid the aggregation phenomenon of CoFe2O4, Figure 6 It can further prove the uniform distribution of Fe, Co, O and C in the magnetic suspension heterogeneous catalyst;
[0169] Depend on Figure 7It can be seen that the Co / Fe atomic ratio in the magnetic suspension heterogeneous catalyst is close to the theoretical stoichiometric ratio in CoFe2O4, which further proves that CoFe2O4 is uniformly distributed in the biochar;
[0170] Depend on Figure 8 It can be seen that the magnetic suspension heterogeneous catalyst is composed of a dark core and a light shell, which match CoFe2O4 and biochar respectively; Fig. 9 It can be seen that the stripe widths of 0.260nm and 0.242nm match the (311) and (222) lattice planes in the CoFe2O4 structure. Figure 1 The XRD spectrum results are consistent with those in .
[0171] (5) Under different pH conditions, the degradation efficiency of lomefloxacin by the magnetic suspension heterogeneous catalysts provided in Examples 1-10, the CoFe2O4 provided in Comparative Example 1, the biomass carbon material provided in Comparative Example 2, the CoFe2O4 composite material provided in Comparative Example 3, the biomass carbon composite material provided in Comparative Example 4, and the heterogeneous catalyst provided in Comparative Example 5 was measured. The measurement conditions were: 0.02 g of the magnetic suspension heterogeneous catalyst and 0.02 g of potassium permonosulfate were added at 25° C., magnetic stirring was performed at 500 r / min, 100 ml of lomefloxacin with an initial concentration of 10 mg / L was taken, and the degradation rate after degradation for 30 min was shown in Table 2. The degradation rates of the magnetic suspension heterogeneous catalyst provided in Example 1 at different pH values are shown in Table 2. Fig.10 The Zeta potential diagram of the magnetic suspension heterogeneous catalyst provided in Example 1, the CoFe2O4 provided in Comparative Example 1, and the biomass carbon material provided in Comparative Example 2 is shown as follows: Fig.11 As shown;
[0172] Depend on Fig.10 It can be seen that the removal rate of lomefloxacin increases with the increase of pH value from 3 to 7, and decreases sharply with the increase of pH value from 11 to 12; Fig.11 It can be seen that the isoelectric point of the magnetic suspension heterogeneous catalyst is measured at 10.55, indicating that the catalyst is positively charged when the solution pH is <10.55, and the catalyst is negatively charged when the solution pH is >10.55; indicating that the pH tolerance range of the magnetic suspension heterogeneous catalyst provided in Example 1 can reach 3-11.
[0173] Table 2
[0174]
[0175]
[0176] (6) The cyclic stability of the magnetically suspended heterogeneous catalysts provided in Examples 1-10, the CoFe2O4 provided in Comparative Example 1, the biomass carbon material provided in Comparative Example 2, the CoFe2O4 composite material provided in Comparative Example 3, the biomass carbon composite material provided in Comparative Example 4, and the heterogeneous catalyst provided in Comparative Example 5 was tested. The test method was to determine the degradation rate (%) of lomefloxacin by the test material during three consecutive uses, and to determine the degradation rate after ultrasonic regeneration for 30 minutes. The results are shown in Table 3.
[0177] The cyclic stability diagram of the magnetic suspension heterogeneous catalyst provided in Example 1 is as follows Fig.12 As shown by Fig.12 It can be seen that after 3 cycles, the degradation rate of lomefloxacin slightly decreased from 83% to 72%, and the catalytic performance can be completely restored after 30 minutes of ultrasound, indicating that the magnetic suspension heterogeneous catalyst provided by the present invention has excellent repeatability and practicality.
[0178] Table 3
[0179]
[0180]
[0181] (7) The antibiotic degradation performance of the magnetically suspended heterogeneous catalysts provided in Examples 1-10, the CoFe2O4 provided in Comparative Example 1, the biomass carbon material provided in Comparative Example 2, the CoFe2O4 composite material provided in Comparative Example 3, the biomass carbon composite material provided in Comparative Example 4, and the heterogeneous catalyst provided in Comparative Example 5 was tested. Deionized water, river water from the Haihe River in Tianjin, and seawater from the Bohai Sea were used to prepare a 10 mg / L lomefloxacin solution, and the degradation rate of lomefloxacin was tested. The test method was to add 0.02 g of potassium permonosulfate at 25°C, stir magnetically at 500 r / min, sample 1 ml after 30 minutes, and detect the absorbance at a wavelength of 280 nm using an ultraviolet spectrophotometer, which was then converted into lomefloxacin concentration. The degradation rate results are shown in Table 4.
[0182] Table 4
[0183] Deionized water (%) River water (%) seawater(%) Example 1 82 56 72 Example 2 82 54 71 Example 3 82 53 68 Example 4 81 55 74 Example 5 75 48 67 Example 6 79 52 65 Example 7 75 46 62 Example 8 74 48 65 Example 9 79 53 71 Example 10 80 52 67 Comparative Example 1 43 27 33 Comparative Example 2 7 3 5 Comparative Example 3 33 18 24 Comparative Example 4 6 3 4 Comparative Example 5 82 56 69
[0184] As can be seen from Table 4, the content of organic pollutants in river water is higher than that in seawater, while the concentration of inorganic ions in river water is much lower than that in seawater. Although the degradation rate of lomefloxacin obtained by the river water matrix is not high, it can still be shown that the magnetic suspension heterogeneous catalyst provided by the present invention can remove most of the lomefloxacin in different types of water and has good antibiotic degradation performance.
[0185] In summary, the present invention provides a magnetic suspension heterogeneous catalyst obtained by a preparation method, and through the use of biochar and a metal source, the metal atoms in the metal source can be evenly dispersed to the surface and pores of the biochar, effectively slowing down the agglomeration of the metal catalyst; moreover, the coordinated use of the biochar and the metal source effectively improves the catalytic activity of the magnetic suspension heterogeneous catalyst. Moreover, the present invention mixes the biochar composite material with hollow glass microspheres and sodium alginate, and composites the powdered material into a spherical shape, overcoming the problem that the powder catalyst is inconvenient to use and difficult to fill a fixed bed, and can also effectively avoid the problem of metal dissolution of metal catalyst species; the use of hollow glass microspheres brings a floating type to the magnetic suspension heterogeneous catalyst, which is conducive to the recovery of the magnetic suspension heterogeneous catalyst.
[0186] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a magnetically suspended heterogeneous catalyst, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing the biochar, the metal source and the solvent, and co-precipitating to obtain a precipitate; (2) The precipitate obtained in step (1) is washed, dried and calcined to obtain a biomass carbon composite material; (3) uniformly mixing the hollow glass microspheres, the thickener solution and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; (4) The mixed solution obtained in step (3) is mixed with the solution and allowed to stand to obtain the magnetically suspended heterogeneous catalyst; The preparation method of the biochar in step (1) comprises the following steps: carbonizing the biomass at 360-420° C. for 1.5-2.5 hours; acid-modifying the biomass after carbonization: soaking the carbonized biomass in an acid solution, washing and drying the biochar in sequence to obtain the biochar; The mass ratio of the hollow glass microspheres to the biomass carbon composite material in step (3) is (0.8-1.2):1; The thickener in the thickener solution of step (3) comprises any one of sodium alginate, chitosan or chitosan, or a combination of at least two thereof; The solution in step (4) includes a calcium salt solution or a sodium hydroxide solution.
2. The preparation method according to claim 1, characterized in that: The biomass charcoal in step (1) includes any one of enteromorpha-based biochar, wood biochar, coconut shell biochar or straw biochar, or a combination of at least two of them.
3. The preparation method according to claim 1, characterized in that: The biochar in step (1) is Enteromorpha-based biochar.
4. The preparation method according to claim 1, characterized in that: The acid solution includes any one of hydrochloric acid solution, nitric acid solution or sulfuric acid solution, or a combination of at least two of them.
5. The preparation method according to claim 1, characterized in that: The acid solution contains H + The concentration is 0.8-1.2mol / L.
6. The preparation method according to claim 1, characterized in that: The soaking time is 1.8-2.4h.
7. The preparation method according to claim 1, characterized in that: The drying temperature in step (1) is 55-65° C. and the drying time is 10-15 hours.
8. The preparation method according to claim 1, characterized in that: The method for preparing biochar in step (1) further comprises ultrasonic alcohol washing after acid modification.
9. The preparation method according to claim 1, characterized in that: The metal source in step (1) includes an iron source and / or a cobalt source.
10. The preparation method according to claim 9, characterized in that: The metal source in step (1) is a combination of an iron source and a cobalt source.
11. The preparation method according to claim 10, characterized in that: The molar ratio of Fe to Co in the metal source of step (1) is (1.8-2.2):
1.
12. The preparation method according to claim 9, characterized in that: The iron source includes FeCl3 and / or Fe(NO3)3.
13. The preparation method according to claim 9, characterized in that: The cobalt source includes CoCl2 and / or Co(NO3)2.
14. The preparation method according to claim 1, characterized in that: The mass ratio of the biochar to the solvent in step (1) is 1:(21-28).
15. The preparation method according to claim 10, characterized in that: The mass ratio of the biochar in step (1) to Co in the metal source is (3-5):
1.
16. The preparation method according to claim 1, characterized in that: The termination pH value of the coprecipitation in step (1) is 9.5-11.
5.
17. The preparation method according to claim 1, characterized in that: The coprecipitation temperature in step (1) is 60-70°C.
18. The preparation method according to claim 1, characterized in that: The coprecipitation time in step (1) is 1.5-2.5h.
19. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 75-85°C.
20. The preparation method according to claim 1, characterized in that: The drying time in step (2) is 10-15 hours.
21. The preparation method according to claim 1, characterized in that: The starting temperature of the calcination in step (2) is 200-240°C, and the end temperature is 660-700°C.
22. The preparation method according to claim 1, characterized in that: The calcination in step (2) includes at least 3 heat preservation processes.
23. The preparation method according to claim 22, characterized in that: The time of the insulation process is 1.8-2.4h.
24. The preparation method according to claim 1, characterized in that: In step (3), the solid-to-liquid ratio of the biomass carbon composite material to the thickener solution is 1:(20-30), and the unit of the solid-to-liquid ratio is g / mL.
25. The preparation method according to claim 1, characterized in that: The concentration of the thickener solution in step (3) is 2-3 wt %.
26. The preparation method according to claim 1, characterized in that: The thickener in the thickener solution of step (3) is sodium alginate.
27. The preparation method according to claim 1, characterized in that: The mixing in step (4) is performed by adding the mixed solution dropwise into the solution.
28. The preparation method according to claim 27, characterized in that: The dropping speed is 2-4 mL / min.
29. The preparation method according to claim 1, characterized in that: The calcium salt in the calcium salt solution includes calcium chloride and / or calcium nitrate.
30. The preparation method according to claim 1, characterized in that: The concentration of the calcium salt solution is 2-4 wt %.
31. The preparation method according to claim 1, characterized in that: The standing time in step (4) is 50-70 minutes.
32. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing Enteromorpha-based biochar, a metal source and water, and co-precipitating at a temperature of 60-70° C. for 1.5-2.5 hours to obtain a precipitate; the termination pH value of the co-precipitation is 9.5-11.5; the mass ratio of Enteromorpha-based biochar to water is 1:(21-28); the mass ratio of Enteromorpha-based biochar to Co in the metal source is (3-5):1; the metal source is a combination of an iron source and a cobalt source, wherein the molar ratio of Fe to Co is (1.8-2.2):1; The preparation method of the enteromorpha-based biochar comprises: carbonizing the enteromorpha at 360-420° C. for 1.5-2.5 h, and then heating the enteromorpha at H + Soaking in an acid solution with a concentration of 0.8-1.2 mol / L for 1.8-2.4 hours, washing, drying at 55-65° C. for 10-15 hours, and then ultrasonically washing with alcohol to obtain the Enteromorpha-based biochar; (2) The precipitate obtained in step (1) is washed, dried at 75-85° C. for 10-15 h, and calcined to obtain a biomass carbon composite material; the starting temperature of the calcination is 200-240° C., the end temperature is 660-700° C., and the calcination process includes at least 3 insulation processes; (3) uniformly mixing the hollow glass microspheres, the sodium alginate solution with a concentration of 2-3wt% and the biomass carbon composite material obtained in step (2) to obtain a mixed solution; the mass ratio of the hollow glass microspheres to the biomass carbon composite material is (0.8-1.2):1; the solid-liquid ratio of the biomass carbon composite material to the sodium alginate solution is 1:(20-30), and the unit of the solid-liquid ratio is g / mL; (4) The mixed solution obtained in step (3) is added dropwise to a calcium salt solution having a concentration of 2-4 wt% at a rate of 2-4 mL / min, and allowed to stand for 50-70 min to obtain the magnetic suspension heterogeneous catalyst.
33. A magnetically suspended heterogeneous catalyst, characterized in that: The magnetic suspension heterogeneous catalyst is obtained by the preparation method described in any one of claims 1-32.
34. A use of the magnetically suspended heterogeneous catalyst as claimed in claim 33, characterized in that: The magnetic suspension heterogeneous catalyst is used for degrading organic pollutants.
Citation Information
Patent Citations
Activated carbon-cobalt ferrite composition material, preparation method thereof and application to photocatalytic denitrification
CN106268819A
Cobalt ferrite / montmorillonite / C catalyst capable of efficiently activating persulfate as well as preparation method and application of cobalt ferrite / montmorillonite / C catalyst
CN112473670A
Ferromagnetic composite ball easy to recycle and application thereof
CN109261133A